Policy Surveillance in the G-20 Fossil Fuel Subsidies Agreement: Lessons for Climate Policy - Joseph E. Aldy (Fondazione Eni Enrico Mattei (FEEM), 2015)
Inadequate policy surveillance has undermined the effectiveness of multilateral climate agreements. To illustrate an alternative approach to transparency, I evaluate policy surveillance under the 2009 G-20 fossil fuel subsidies agreement. The Leaders of the Group of 20 nations tasked their energy and finance ministers to identify and phase-out fossil fuel subsidies. The G-20 leaders agreed to submit their subsidy reform strategies to peer review and to independent expert review conducted by international organizations. This process of developed and developing countries pledging to pursue the same policy objective, designing and publicizing implementation plans, and subjecting plans and performance to review by international organizations differs considerably from the historic approach under the UN Framework Convention on Climate Change. This paper draws lessons from the fossil fuel subsidies agreement for climate policy surveillance.
Keywords: F53; H23; Q40; 330; Transparency; Pledge and Review; International Environmental Agreements